2019
DOI: 10.1021/acs.chemmater.9b01734
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Oxide Ion Conductivity in the Langasite Structure: Carrier Trapping by Formation of (Ga,Ge)2O8 Units in La3Ga5–xGe1+xO14+x/2 (0 < x ≤ 1.5)

Abstract: Framework oxides with the capacity to host mobile interstitial oxide anions are of interest as electrolytes in intermediate temperature solid oxide fuel cells (SOFCs). High performance materials of this type are currently limited to the anisotropic oxyapatite and melilite structure types. The langasite structure is based on a corner-shared tetrahedral network similar to that in melilite but is three-dimensionally connected by additional octahedral sites that bridge the layers by corner sharing. Using low-tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 60 publications
5
49
0
Order By: Relevance
“…Recent studies suggest that non-equilibrium synthesis methods can be used to exceed such compositional limits. For example, a sol-gel approach with annealing at moderate temperatures drastically extends the accessible interstitial oxide concentration range in langasite-type La3Ga5-xGe1+xO14+x/2; 21 whilst the synthesis of metastable melilites including the nonstoichiometric aluminates La1+xCa1-xAl3O7+x/2 (x ≤ 0.6) and a range of stoichiometric and nonstoichiometric small-A-site compositions, which cannot be achieved by high temperature ceramic routes, is made possible by crystallization-fromglass. 8,10,22 A recent study of (1-y)La2O3 -(y)Ga2O3 glasses by ADL-laser heating found that y = 0.40 was difficult to vitrify despite lying well within the limits of the glass-forming region (0.20 ≤ y ≤ 0.55), hinting at the presence of an unknown metastable compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that non-equilibrium synthesis methods can be used to exceed such compositional limits. For example, a sol-gel approach with annealing at moderate temperatures drastically extends the accessible interstitial oxide concentration range in langasite-type La3Ga5-xGe1+xO14+x/2; 21 whilst the synthesis of metastable melilites including the nonstoichiometric aluminates La1+xCa1-xAl3O7+x/2 (x ≤ 0.6) and a range of stoichiometric and nonstoichiometric small-A-site compositions, which cannot be achieved by high temperature ceramic routes, is made possible by crystallization-fromglass. 8,10,22 A recent study of (1-y)La2O3 -(y)Ga2O3 glasses by ADL-laser heating found that y = 0.40 was difficult to vitrify despite lying well within the limits of the glass-forming region (0.20 ≤ y ≤ 0.55), hinting at the presence of an unknown metastable compound.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that non-equilibrium synthesis methods can be used to exceed such compositional limits. For example, a sol–gel approach with annealing at moderate temperatures drastically extends the accessible interstitial oxide concentration range in langasite-type La 3 Ga 5– x Ge 1+ x O 14+ x /2 , while the synthesis of metastable melilites including the non-stoichiometric aluminates La 1+ x Ca 1– x Al 3 O 7+ x /2 ( x ≤ 0.6) and a range of stoichiometric and nonstoichiometric small-A-site compositions, which cannot be achieved by high-temperature ceramic routes, is made possible by crystallization from glass. ,, …”
mentioning
confidence: 99%
“…According to the 71 Ga MAS NMR study reported by Lopez et al, the chemical shifts of 4-, 5-, and 6-coordinated Ga of La 3 Ga 5−x Ge 1+x O 14+x/2 crystals were confirmed at ∼250, ∼150, and ∼30 ppm, respectively. 35 Therefore, the broad signals at 100−300 ppm observed in both 3L7G and 5L5G are estimated to be an overlap of the two signals due to 4-and 5-coordinated Ga. The above results suggest that the La 2 O 3 −Ga 2 O 3 glass has 4−6coordinated Ga and that the Ga-rich glass has a higher fraction of the six-coordinated Ga than La-rich glass.…”
Section: Resultsmentioning
confidence: 75%
“…This indicates that the fraction of 6-coordinated Ga in La-rich glass is small. According to the 71 Ga MAS NMR study reported by Lopez et al, the chemical shifts of 4-, 5-, and 6-coordinated Ga of La 3 Ga 5– x Ge 1+ x O 14+ x /2 crystals were confirmed at ∼250, ∼150, and ∼30 ppm, respectively . Therefore, the broad signals at 100–300 ppm observed in both 3L7G and 5L5G are estimated to be an overlap of the two signals due to 4- and 5-coordinated Ga.…”
Section: Resultsmentioning
confidence: 83%
“…The langasite structure, of general formula A 3 BC 3 D 2 O 14 , is a layered framework structure type constructed from corner-sharing (C,D)­O 4 tetrahedra and BO 6 octahedra; the BO 6 octahedra also bridge adjacent layers, forming 8-coordinate interlayer sites for A cations, which are arranged in channels along the stacking axis (Figure ). The structure type, which is of interest for properties arising from its polarity, ,, optical transparency, , or ability to host interstitial oxide ions, can accommodate multiple cations with different coordination preferences: the A sites tend to host alkaline- and rare-earth cations, while transition metal and p -block cations tend to be distributed across the corner-linked B, C, and D sites. Ca 3 Ga 2 Ge 4 O 14 is readily synthesized in bulk and adopts the common trigonal langasite structure (space group P 321).…”
Section: Introductionmentioning
confidence: 99%